Reciprocal influences of tobacco use on illicit opioid and alcohol use during the first six-months of specialist addiction treatment. (1st January 2021) - Eastwood, Brian; Clare, Tom; Dockrell, Martin J.; Locker, Jo; Chowdary, Qasim; Jahr, Stefan; Jones, Andrew; Robson, Deborah; Marsden, John
Highlights: Tobacco smoking is highly prevalent in patients starting specialist addiction treatment for illicit opioids or alcohol. During the first six-months of treatment, OUD and AUD patients reduce the frequency of use of illicit opioids or alcohol. Non-significant reductions in tobacco use in these cohorts were also recorded. Higher smoking frequency at admission is associated with higher illicit opioid and alcohol use frequency after six-months of specialist addiction treatment. Abstract: Background: This is the first national study of lagged reciprocal associations between tobacco smoking frequency and change in illicit opioid or alcohol use frequency within six-months of treatment. Methods: All adults admitted to publicly-funded specialist addiction treatment in England in 2018/19 and enrolled for at least six months for either opioid use disorder (OUD; n = 22, 046; 82.4 % of those eligible) or alcohol use disorder (AUD; n = 15, 251; 78.8 % of those eligible). Two cross-lagged panel models estimated, separately for OUD and AUD patients, the relationships between smoking at admission and change in main drug over six months, and between main drug use at admission and change in smoking over six months. Results: Within the OUD cohort, illicit opioid use frequency reduced from 17.7 days to 8.0 days and smoking tobacco remained at 18.8 days. After controlling for available covariates, higher smoking frequency at admission was associated with a relative increase in illicit opioid use at six-months (0.02 days [95 % CI 0.00−0.03]). Within the AUD cohort, alcohol use frequency reduced from 21.2 days to 14.4 days while smoking tobacco reduced from 12.6 days to 11.5 days. Higher smoking frequency at admission was associated with a relative increase in alcohol use at six-months (0.03 days [95 % CI 0.02−0.04]) and higher alcohol use frequency at admission was associated with a relative increase in smoking at six-months (0.04 [95 % CI 0.02−0.06]), controlling for available covariates. Conclusions: Higher smoking frequency at admission is associated with higher illicit opioid and alcohol use frequency after six-months of specialist addiction treatment.